2021
DOI: 10.5694/mja2.50992
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of paracetamol for pain relief: an overview of systematic reviews

Abstract: Objective To evaluate the efficacy and safety of paracetamol as an analgesic medication in a range of painful conditions. Study design Systematic review of systematic reviews of the analgesic effects of paracetamol in randomised, placebo‐controlled trials. Conduct of systematic reviews was assessed with AMSTAR‐2; confidence in effect estimates (quality of evidence) was assessed with the Grading of Recommendations Assessment, Development and Evaluation (GRADE) criteria. Data sources MEDLINE, EMBASE, PsycINFO, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…The numbers of studies, systemic reviews, and meta-analyses on paracetamol is high and growing. However, large, authoritative clinical trials are costly, and it is unclear whether they will be done [ 145 , 146 ].…”
Section: Recent Findings and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The numbers of studies, systemic reviews, and meta-analyses on paracetamol is high and growing. However, large, authoritative clinical trials are costly, and it is unclear whether they will be done [ 145 , 146 ].…”
Section: Recent Findings and Future Directionsmentioning
confidence: 99%
“…Recently, Abdel Shaheed analyzed data from 36 publications and reported that paracetamol produced modest pain relief in hip and knee osteoarthritis, tension headache, and post-craniotomy pain and that it was ineffective in other conditions [ 145 ]; the authors concluded with the need for large, high-quality trials to reduce uncertainty about the efficacy of paracetamol in common pain conditions. In the last few months, new published studies report the safe use of paracetamol in patients with chronic kidney disease [ 147 ], the significant efficacy of paracetamol for post-arthroplasty pain [ 148 ], the lesser efficacy of paracetamol than ibuprofen for post-laminectomy pain [ 149 ], the opioid-sparing effects of paracetamol in the Emergency Department [ 150 ], the recommendations against paracetamol in lumbar spinal stenosis with neurogenic claudication [ 151 ], and the recommendations in favor of paracetamol for postcesarean pain [ 152 ] and for migraine [ 153 , 154 ].…”
Section: Recent Findings and Future Directionsmentioning
confidence: 99%
“…Its efficacy in other painful conditions is uncertain. 20 In view of an increased risk of hepatotoxicity in older adults, sometimes at therapeutic doses, 21,22 and emerging evidence of a relative lack of efficacy of paracetamol, the benefits of long-term use need to be re-evaluated. Co-administration of paracetamol with other analgesics is common, however there is a lack of data on the efficacy of combination therapy in chronic non-cancer pain.…”
Section: Paracetamolmentioning
confidence: 99%
“…Differential use of co-interventions might lead to underestimation or overestimation of treatment effects 21112. Many placebo controlled trials of pain interventions, for example, report small or non-existent benefits 13. But these studies often allow pain relieving co-interventions while failing to record the type, frequency, or duration of co-interventions used in each study arm.…”
Section: Unbiased Comparisonsmentioning
confidence: 99%